Distribution of polyprenol and dolichol in oil palms from Pisifera parents and mature plants from tissue culture propagation - Luthfi Aziz Mahmud Siregar; ERKY BEBY AYU KARTIKA; MOHAMMAD BASYUNI (Society for Indonesian Biodiversity, 2021)
Abstract. Kartika EBA, Siregar LAM, Basyuni M. 2021. Distribution of polyprenol and dolichol in oil palms from Pisifera parents and mature plants from tissue culture propagation. Biodiversitas 22: 3423-3436. Oil palm tissue culture is carried out through indirect embryogenesis, which causes somaclonal diversity to occur at the in vitro propagation stage, especially in the callus growth phase. In the cells of all living organisms can be found a group of polyisoprenoid compounds. This study aims to determine variations in oil palm plants resulting from tissue culture based on the presence of polyisoprenoid compounds. Oil palm leaf samples (Elaeis guineensis Jacq.) were collected from the plantation of PT. Socfin Indonesia, North Sumatra, Indonesia. Sample extraction, saponification, isolation of polyisoprenoid compounds, and two-dimensional thin-layer chromatography analysis were carried out to obtain data related to total lipids, polyprenol and dolichol profile, and Carbon (C) chain length polyprenol and dolichol from oil palm leaves of Pisifera parents and their propagated derivatives by indirect embryogenesis. The results showed that the amount of polyisoprenoid mother S24 was 2.41 mg/g higher than that of the parentS8 at 2.17 mg/g dry weight. Total polyisoprenoid fromS8 plants in vitro ranged from 0.71 - 8.53 mg/g dry weight, with the lowest total polyisoprenoid found atS894/22 and the highest was found atS893/2. While for total polyisoprenoid from plant tissue culture of Pisifera S24 ranged from 0.73 - 8.05 mg/g dry weight, with the lowest total polyisoprenoid found at S24H14 and the highest was found at S24H16. The parent plants of Pisifera S8 and S24, as well as plants resulting from tissue culture, were categorized as having lipid pattern type II, which showed a balanced distribution of polyprenol with dolichol. The longest carbon chain was found in vitro plantsS8 93/4 ranged from C50-C110, while the shortest was found in plants produced in vitro S24H7 starting from C45-C55. There were variations in the carbon chain length of polyprenol and dolichol in the leaf samples derived from in vitro propagation of the Pisifera S8 and S24 parents.